Infrared Nanospectroscopy Reveals the Chemical Nature of Pit Membranes in Water-Conducting Cells of the Plant Xylem. Issue 4 (5th June 2018) - Pereira, Luciano; Flores-Borges, Denisele N.A.; Bittencourt, Paulo R.L.; Mayer, Juliana L.S.; Kiyota, Eduardo; Araújo, Pedro; Jansen, Steven; Freitas, Raul O.; Oliveira, Rafael S.; Mazzafera, Paulo
Abstract : Intervessel pit membranes have a complex chemical composition in water-conducting cells of Populus nigra xylem. Abstract: In the xylem of angiosperm plants, microscopic pits through the secondary cell walls connect the water-conducting vessels. Cellulosic meshes originated from primary walls, and middle lamella between adjacent vessels, called the pit membrane, separates one conduit from another. The intricate structure of the nano-sized pores in pit membranes enables the passage of water under negative pressure without hydraulic failure due to obstruction by gas bubbles (i.e. embolism) under normal conditions or mild drought stress. Since the chemical composition of pit membranes affects embolism formation and bubble behavior, we directly measured pit membrane composition in Populus nigra wood. Here, we characterized the chemical composition of cell wall structures by synchrotron infrared nanospectroscopy and atomic force microscopy-infrared nanospectroscopy with high spatial resolution. Characteristic peaks of cellulose, phenolic compounds, and proteins were found in the intervessel pit membranes of P. nigra wood. In addition, the vessel to parenchyma pit membranes and developing cell walls of the vascular cambium showed clear signals of cellulose, proteins, and pectin. We did not find a distinct peak of lignin and other compounds in these structures. Our investigation of the complex chemical composition of intervessel pit membranes furthers our understanding of the flow of water and bubbles between neighboring conduits. The advances presented here pave the way for further label-free studies related to the nanochemistry of plant cell components.